Dari Teori ke Kesalahan: Memetakan Deviasi Pola Kalimat Dasar Bahasa Indonesia - Desta Aditya; Usamah Abdul Aziz; Agung Pranoto Kadiatmaja (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to identify, classify, and explain various deviations in Indonesian basic sentence patterns based on syntactic theory and error analysis. The research employed a descriptive qualitative approach with data consisting of 50 sentences containing deviations from basic sentence patterns. The data were purposively collected from students’ compositions, students’ scientific articles, and online media texts. Data collection was conducted through observation and note-taking techniques, while data analysis involved identification, classification, interpretation, and explanation of errors based on Indonesian syntactic theory. The findings reveal five major types of deviations: subject omission (24%), predicate omission (16%), misplacement of sentence elements (30%), syntactic function mismatch (20%), and redundancy (10%). Misplacement of sentence elements was found to be the most dominant type of deviation. These findings indicate a gap between the theoretical understanding of syntax and the practical use of Indonesian sentence structures in various contexts. This study contributes to the fields of syntax and error analysis and may serve as a reference for improving Indonesian language teaching and learning.